POSTMODERNISMUL - CADRU AL DIVERSITĂŢII EDUCAŢIONALE - USM ADMIN (Moldova State University, 2010)
Postmodernity is the age of thinking, not so much of fragmentation, as of plurality, even the shift from unity to plurality is a form of our existence. Diversity is both an intrinsic attribute of nature and culture. As regards culture, without diversity, it would be empty, without any content. Values, beliefs, symbols, attitudes, mentalities, habits, morals, ethical standards are elements of culture that distinguish people, social groups, communities, and nations. Even if there is a common moral core, people are different depending on the elements of culture they are identified with.